Assessment of Marital Dissatisfaction among Divorces in Women Continuing Education Centre, Sokoto, Sokoto State, Nigeria - Yusuf, Murtala Akanbi; Alkali, Muhammad (International Journal for Educational and Vocational Studies, 2020)
The study examined marital dissatisfaction among divorces in Women Continuing Education Centre Sokoto, Sokoto state, Nigeria. The study used descriptive research design to examine the level of marital dissatisfaction among divorces and reasons for marital dissatisfaction among divorces Women Continuing Education Centre Sokoto. The population of this study was all 579 divorcees in Women Continuing Education Centre, Sokoto and a sample size of 354 divorcees consented to participate in the study. The researchers used Marital Dissatisfaction Scale (MDS) and Factors for Marital Dissatisfaction Questionnaire (FMDQ) with reliability indexes of 0.75 for and 0.83 respectively. The research questions were answered with use of frequency and percentages. The findings revealed that many couples seek for when they are dissatisfied with their marriage. And marital dissatisfaction happens when marital expectations do not forthcoming. The study recommended that efforts in form of enlightenment and mobilization should be put in place by adult educators for couples in order to ensure that every partner plays his/her role in ensuring marital satisfaction.